TOPICAL APPLICATION OF Capsicum frutescens LEAF EXTRACT AS HAIR TONIC IN MICE (Mus musculus) - Safrida Safrida; Shella Nasmi; Devi Syafrianti (Universitas Syiah Kuala, 2020)
The research aims to determine the effect of giving cayenne leaf extract in increasing the length and amount of hair on mice. This research belongs to the type of quantitative research. This research used a Completely Randomized Design (CRD) in consisting of 5 treatment and 4 repetitions. The treatments consisted of NC (negative control, not treated), PC (positive control, given a commercial hair extract), P1 (cayenne leaf extract 10%), P2 (cayenne leaf extract 20%), and P3 (cayenne leaf extract 30%). Research parameters included the increase of the hair length and amount of hairs growing in mice. The result showed that giving extract of cayenne leaf significantly influences the length and amount of hairs in mice, with 10% concentration (P2) was the optimum concentration of the extract that can trigger the hair growth. It can be concluded that given extract of cayenne leaf can increase the hairs growth in mice and has potential as hair tonic.